2013
DOI: 10.3109/14767058.2013.818120
|View full text |Cite
|
Sign up to set email alerts
|

Early regular versus late selective poractant treatment in preterm infants born between 25 and 30 gestational weeks: a prospective randomized multicenter study

Abstract: ES treatment decreases IVH (≥ grade III) and pneumothorax rates but does not have any effect on BPD when compared to LS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…The searches of the electronic databases and gray literature identified 1761 nonduplicate records, among which 62 articles were selected for full-text review ( Figure 1) and 9 trials met the inclusion criteria, [27][28][29][30][31][32][33][34][35] with a total of 1551 preterm infants. The agreement of the study selection between the 2 reviewers was excellent, with a κ of 0.828 and a raw agreement of 95.2%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The searches of the electronic databases and gray literature identified 1761 nonduplicate records, among which 62 articles were selected for full-text review ( Figure 1) and 9 trials met the inclusion criteria, [27][28][29][30][31][32][33][34][35] with a total of 1551 preterm infants. The agreement of the study selection between the 2 reviewers was excellent, with a κ of 0.828 and a raw agreement of 95.2%.…”
Section: Resultsmentioning
confidence: 99%
“…Because all the outcomes were objective, the detection bias attributable to the lack of masking was considered low risk for most of the outcomes except for CLD, whose diagnoses might be affected by the different criteria of oxygen administration among physicians. 36 The data for CLD in the study by Dilmen et al 27 and for severe intraventricular hemorrhage in the study by Verder et al 35 were judged as being at high risk of attrition bias due to missing data (>10%). Two studies 34,35 were stopped early for significant findings that may overestimate intervention effects 37 and, hence, were considered at high risk of bias.…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%
“…With regard to avoiding eMV, nine RCTs were included. These RCTs compared various strategies of nCPAP with or without surfactant administration via a thin catheter versus strategies that prescribed INSURE or longer-term eMV and surfactant (table 2) [13,[21][22][23][24][25][26][27][28].…”
Section: Included Studiesmentioning
confidence: 99%
“…Only two RCTs in the sustained inflations meta-analysis prescribed a blinded outcome assessment (low risk/detection bias) [12,20]. Minor issues in several studies were the incomplete description of random sequence generation (unclear risk/selection bias) [17-19, 23, 24, 27], late or no registration of the study protocol (unclear risk/reporting bias) [11,18,19,22,27,28], and the use of respiratory distress as a study entry criterion (unclear risk/sampling bias) [13,21,22,26,28]. Other risks of bias in individual studies and the support for the current review authors' judgements are described in the supplementary material.…”
Section: Risk Of Bias In the Included Studiesmentioning
confidence: 99%
“…4,5 However, recent meta-analysis have shown that this practice of prophylactic use of surfactant is no more superior to early selective treatment with surfactant as soon as the clinical signs of RDS appear. [6][7][8][9] A major long term morbidity of premature birth is Bronchopulmonary dysplasia which is defined as a need for supplemental oxygen or ventilatory support at 36 weeks post last menstrual period (LMP). This is a clinical sequela of prolonged ventilation as a result of abnormal reparative processes in response to injury and inflammation.…”
mentioning
confidence: 99%